QURANIC-BASED BASIC MATHEMATICS COURSE FOR STUDENTS IN ISLAMIC UNIVERSITIES - Mahdalena, Mahdalena; Nurlaila, Nurlaila (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
At the State Islamic Ministry College (PTKIN), one of the subjects or courses (MK) offered to undergraduate students is basic mathematics. This subject is taught in the first semester to give students the necessary knowledge, skills, or abilities to solve problems. Given the wide range of applications of mathematics, mathematics must be taught in a way connected with religion. The PTKIN document contrasts PTKIN and general universities, which includes this issue. This study aims to provide insights or opinions about the content of the primary mathematics curriculum based on the Al Quran. The author's primary sources for this bibliographic approach are the Al Quran, math articles with an Islamic context, and math publications based on the Al Quran. Other supplementary materials are from articles and math textbooks that are not contextualized within the Islamic framework. One of the various versions that may be utilized as teaching materials for lecturers in this MK is provided in student worksheets and handouts for statistics-related courses.